The complete chloroplast genome of Sargassum fusiforme - Liu, Tao (Mitochondrial DNA B Resour, 2020)
The complete chloroplast genome sequence of Sargassum fusiforme is presented here. Circular mapping revealed that the complete chloroplast DNA sequence of S. fusiforme was 124,298 bp in length and had an overall AT content of 69.57%, including 137 protein-coding genes, 2 open reading frames, 28 transfer RNA genes, and 6 ribosomal RNA genes. The phylogenetic tree based on Bayesian shows that all kinds of Phaeophyceae were clustered into two monophyletic groups.